THE POSSIBILITIES OF DISJUNCTION IN THE MENTAL MODELS THEORY - Astorga, Miguel López (2018)
Baratgin and colleagues have questioned certain aspects of the mental models theory related to disjunction. It is truth that, from this last theory, the paper authored by Baratgin et al. (2015) has already been responded. However, I try to further develop that response here by insisting in two important points of the theory: the role that modulation plays in it and the clear differences between its framework and standard logic. In this way, my main aim is to support to a larger extent, by means of theoretical arguments based on its general approach, the idea that the objections presented in the mentioned paper do not really impact the mental models theory.